Terapi Meditasi (Dzikir) Untuk Mengurangi Stres Pada Perempuan dengan Kasus Onkologi - aim matun nadhiroh (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: The primary cancer treatment may include surgery, radiotherapy, chemotherapy and hormone therapy. Surgery aims to remove the cancerous mass and correct any complications that may occur. Undergoing surgery will cause stress to the patient both psychologically and physiologically. Stress and anxiety are caused by the patient's perception of the operating room as a foreign and threatening environment, s separation from family members and friends, and the possibility of a bad prognosis that can affect the patient's future. An excellent emotional management strategy is expected to improve individuals' subjective well-being so that they can achieve peace of mind such as gratitude, patience, love of Allah, and expecting Allah's reward by doing meditation therapy in the form of dhikr. This study aimed to determine the effect of dhikr meditation therapy on reducing stress levels in women with oncology cases.Methods: This study used a pre-experimental design with a one-group pretest-posttest design. This research was conducted by giving pre-test and post-test before and after the dhikr intervention. The population in this study were all women oncology cases at the Haji Hospital, East Java Province, Surabaya, using purposive sampling, a technique so that a total sample of 15 people was obtained. This study was conducted on January 2022. Two data collection instruments’ names lent any of the instrument respondents to assess women's stress levels with oncology cases. Furthermore, the data were analysed univariate and bivariate with paired t-test results. Kolmogorov-Smirnov’s pretest probability value of the dhikr experiment is 0.200, and the post-test of the dhikr experiment is 0.200. This indicates that the experimental group of dhikr is normally distributed. Based on the statistical test in table 4, the p-value (0.001) is obtained.Results: Kolmogorov-Smirnov’s pretest probability value of the dhikr experiment is 0.200, and the post-test of the dhikr experiment is 0.200. This indicates that the experimental group of dhikr is normally distributed. Based on the statistical test in table 4, the p-value (0.001) is obtained.Conclusion: There is a significant difference before and after dhikr on reducing stress levels in women with oncology cases. Midwives should consider making dhikr to treat psychological problems (especially stress) in women with oncology cases.